Time course of lesion-induced atrophy in multiple sclerosis - Carolus, Keith; Fuchs, Tom A; Bergsland, Niels; Ramasamy, Deepa; Tran, Hoan; Uher, Tomas; Horakova, Dana; Vaneckova, Manuela; Havrdova, Eva; Benedict, Ralph H B; Zivadinov, Robert; Dwyer, Michael G (Journal of neurology, 2022)
BACKGROUND AND PURPOSE: White matter (WM) tract disruption impacts volume loss in connected deep gray matter (DGM) over 5 years in people with multiple sclerosis (PwMS). However, the timeline of this phenomenon remains poorly characterized. MATERIALS AND METHODS: Annual serial MRI for 181 PwMS was retrospectively analyzed from a 10-year clinical trial database. Annualized thalamic atrophy, DGM atrophy, and disruption of connected WM tracts were measured. For time series analysis, ~700 epochs were collated using a sliding 5-year window, and regression models predicting 1-year atrophy were applied to characterize the influence of new tract disruption from preceding years, while controlling for whole brain atrophy and other relevant factors. RESULTS: Disruptions of WM tracts connected to the thalamus were significantly associated with thalamic atrophy 1 year later (β: 0.048-0.103). This effect was not observed for thalamic tract disruption concurrent with the time of atrophy nor for thalamic tract disruption preceding the atrophy by 2-4 years. Similarly, disruptions of white matter tracts connected to the DGM were significantly associated with DGM atrophy 1 year later (β: 0.078-0.111), but not for tract disruption concurrent with, nor preceding the atrophy by 2-4 years. CONCLUSION: Increased rates of thalamic and DGM atrophy were restricted to 1 year following newly developed disruption in connected WM tracts. In research and clinical settings, additional gray matter atrophy may be expected 1 year following new lesion growth in connected white matter.
Keywords: Magnetic Resonance Imaging; šedá hmota; Gray Matter; White Matter; Lesions; lidé; Multiple Sclerosis; magnetická rezonanční tomografie; roztroušená skleróza; mozek; atrofie; retrospektivní studie; Atrophy; Brain; Degeneration; Multiple sclerosis; Retrospective Studies; bílá hmota; Humans